THE IMPACT OF HEALTH SAFETY MANAGEMENT AND SERVICE QUALITY ON CUSTOMER SATISFACTION IN LOGISTICS: A MEDIATED MODEL FROM THAILAND - Jotikasthira, Chotima; Srivarapongse, Tassin; Onputtha, Suraporn (Asian Administration and Management Review, 2025)
This research investigates the impact of health safety management (HSM) and service quality (SQ) on customer satisfaction (SAT) within the logistics service provider (LSP) context in Thailand, examining the mediating role of customer decision-making (DCS). Utilizing a structured questionnaire administered to 400 logistics service users and analyzed using structural equation modeling (SEM), the study reveals that effective HSM has a positive influence on customer decision-making, ultimately enhancing customer satisfaction. Moreover, high SQ also significantly improves SAT through customer decision-making. The research highlights the significance of customer decision-making as a crucial mediator between HSM and SQ, as well as customer satisfaction. While the direct impact of HSM on SAT was not significant, its influence was notable. This study provides practical insights for logistics companies seeking to enhance customer satisfaction, emphasizing the importance of robust safety standards, improved service delivery, and a supportive environment that fosters favorable customer decision-making. The findings contribute to the academic understanding of the mediating effect of customer decision-making and offer strategic guidance for logistics providers.